2018
DOI: 10.4314/jfas.v9i5s.8
|View full text |Cite
|
Sign up to set email alerts
|

Personal strategic planning mobile application: preliminary study

Abstract: An important aspect of successful personal planning is to promote the individual to commit to his own plans. Although of the importance of personal planning in all aspects of individuals' daily life and future, failure is a predictable result of a non-well managed and written plans.Hence, smartphones nowadays become a necessity for individuals their usage in daily life has become a basic need. With the recent advances in the capabilities of smartphones and their growing penetration rate among the individuals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In view of online touchpoints, many companies use mobile apps as a major tool to engage with their customers. With this development, many scholars have studied the quality elements of mobile apps with customer experiences in various industries (Bahtar, 2018;Hallikainen et al, 2019;Wu & Ho, 2022). For instance, Wu and Ho (2022) highlighted most of the quality variables of mobile touchpoints, like information, design, and functions, have significant differences with the types of customers in Taiwan.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of online touchpoints, many companies use mobile apps as a major tool to engage with their customers. With this development, many scholars have studied the quality elements of mobile apps with customer experiences in various industries (Bahtar, 2018;Hallikainen et al, 2019;Wu & Ho, 2022). For instance, Wu and Ho (2022) highlighted most of the quality variables of mobile touchpoints, like information, design, and functions, have significant differences with the types of customers in Taiwan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Wu and Ho (2022) highlighted most of the quality variables of mobile touchpoints, like information, design, and functions, have significant differences with the types of customers in Taiwan. Also, Bahtar (2018) revealed that information quality and security have helped to reduce customer effort and led to customer loyalty. Moreover, Parise et al (2016) claimed that mobile app design and functional quality helped improve customer effort scores and customer experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They added that mobile apps enable customers to access services anytime, anywhere, and enhance their convenience in engaging with the companies. On another note, Bahtar (2018) revealed that information quality and security have helped to reduce Online ISSN: 1994-1633/ Print ISSN: 1994-1625 DOI: 10.55951/nurture.v17i3.317| URL: www.nurture.org.pk customer effort and led to customer loyalty. Similarly, Parise, Guinan, and Kafka (2016) also claimed that mobile app design and functional quality helped improve customer effort scores and customer experience.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile business application that provides personalization content, incorporate valuable features and provide exceptional customer services leads to increase customer loyalty, improve customer service through availability of resources (Bahtar, 2018). It improves customer loyalty, improves customer engagement, provide push notifications, helps in retargeting and provide personalized shopping experience thus leads to increase company revenue through utilization of resources (Hussain & Mkpojiogu, 2015).…”
mentioning
confidence: 99%